High Effectiveness in Actions of Carfilzomib on Delayed-Rectifier K+ Current and on Spontaneous Action Potentials - So, Edmund Cheung; Liu, Ping-Yen; Lee, Chien-Ching; Wu, Sheng-Nan (Frontiers in Pharmacology, 2019)
Carfilzomib (CFZ, Kyprolis®) is widely recognized as an irreversible inhibitor of proteasome activity; however, its actions on ion currents in electrically excitable cells are largely unresolved. The possible actions of CFZ on ionic currents and membrane potential in pituitary GH3, A7r5 vascular smooth muscle, and heart-derived H9c2 cells were extensively investigated in this study. The presence of CFZ suppressed the amplitude of delayed-rectifier K+ current (IK(DR)) in a time-, state-, and concentration-dependent manner in pituitary GH3 cells. Based on minimal reaction scheme, the value of dissociation constant for CFZ-induced open-channel block of IK(DR) in these cells was 0.33 uM, which is similar to the IC50 value (0.32 uM) used for its efficacy on inhibition of IK(DR) amplitude. Recovery from IK(DR) block by CFZ (0.3 uM and 1 uM) could be well fitted by single exponential with 447 and 645 ms, respectively. The M-type K+ current, another type of K+ current elicited by low-threshold potential, was slightly suppressed by CFZ (1 uM). Under current-clamp condition, addition of CFZ depolarized GH3 cells, broadened the duration of action potentials as well as raised the firing frequency. In A7r5 vascular smooth muscle cells or H9c2 cardiac cells, the CFZ-induced inhibition of IK(DR) remained efficacious. Therefore, our study led us to reflect that CFZ or other structurally similar compounds should somehow act on the activity of membrane KV channels through which they influence the functional activities in different types of electrically excitable cells such as endocrine, neuroendocrine cells, smooth muscle cells, or heart cells, if similar in vivo findings occur.